Cultivating Empathy through Communication: Understanding Others to Improve Relationships - Yasin Husain (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Understanding and sharing another person's emotions is a necessary skill for building rapport and sharing ideas. It might be challenging to cultivate empathy in a world where people so frequently prioritize their own needs and points of view. In light of the current political split and the COVID-19 epidemic, this research explores the implications of empathy in these two very different contexts. Empathy is emphasized as a means to better relationships and a more caring society. We examine specific methods and strategies for encouraging empathy in everyday interactions and emphasize the benefits of empathic communication. By highlighting the importance of empathy and providing tangible techniques to enhance it through communication, this article aims to assist individuals and communities in building deeper understanding, connection, and well-being.